Diffusion Tensor Imaging for Surgical Planning in Patients with Cervical Spondylotic Myelopathy - Schöller, Karsten; Siller, Sebastian; Brem, Christian; Lutz, Jürgen; Zausinger, Stefan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Study Aims/Objective Despite its invasiveness, computed tomography myelography (CTM) is still considered an important supplement to conventional magnetic resonance imaging (MRI) for preoperative evaluation of multilevel cervical spondylotic myelopathy (CSM). We analyzed if diffusion tensor imaging (DTI) could be a less invasive alternative for this purpose.Material and Methods In 20 patients with CSM and an indication for decompression of at least one level, CTM was performed preoperatively to determine the extent of spinal canal/cerebrospinal fluid (CSF) space and cord compression (Naganawa score) for a decision on the number of levels to be decompressed. Fractional anisotropy (FA) and apparent diffusion coefficient (ADC) were correlated with these parameters and with MRI-based increased signal intensity (ISI). Receiver operating characteristic analysis was performed to determine the sensitivity to discriminate levels requiring decompression surgery. European Myelopathy Score (EMS) and neck/radicular visual analog scale (VAS-N/R) were used for clinical evaluation.Results According to preoperative CTM, 20 levels of maximum and 16 levels of relevant additional stenosis were defined and decompressed. Preoperative FA and particularly ADC showed a significant correlation with the CTM Naganawa score but also with the ISI grade. Furthermore, both FA and ADC facilitated a good discrimination between stenotic and nonstenotic levels with cutoff values < 0.49 for FA and > 1.15 × 10−9 m2/s for ADC. FA and especially ADC revealed a considerably higher sensitivity (79% and 82%, respectively) in discriminating levels requiring decompression surgery compared with ISI (55%). EMS and VAS-N/R were significantly improved at 14 months compared with preoperative values.Conclusion DTI parameters are highly sensitive at distinguishing surgical from nonsurgical levels in CSM patients and might therefore represent a less invasive alternative to CTM for surgical planning.
Keywords: cervical spondylotic myelopathy; diffusion tensor imaging; computed tomography myelography; magnetic resonance imaging